The European Organization for Research and Treatment for Cancer (EORTC) strategy for quality assurance in surgical clinical research: Assessment of the past and moving towards the future. Issue 8 (August 2016) - Tanis, E.; Caballero, C.; Collette, L.; Verleye, L.; den Dulk, M.; Lacombe, D.; Schuhmacher, C.; Werutsky, G.
Abstract: Aims: Quality assurance (QA) in a surgical trial must be planned and implemented from study development to completion. Elements of quality must be consistently described in a protocols, case report forms (CRFs) and reported in publications. The purpose of this review was to evaluate the most common surgical parameters and how consistently they were described in EORTC study documents where surgery was included. This was the preliminary step in mapping out the challenges of developing a surgical QA strategy in EORTC. Methods: A systematic review of EORTC surgical protocols from 1980 to 2013 was performed. Two independent reviewers selected and reviewed the protocols. Data extraction was done using a questionnaire developed by EORTC QA committee. The results were compared across the time period. Results: The most common quality parameters described in protocols were surgical technique, definition of resectability, surgical margins and methods of assessing adverse events using the Common Terminology Criteria for Adverse Event (CTCAE). However, these were not consistently reported in publications. A general improvement in the method of protocol development was observed since year 2000 after standardization measures by EORTC. A new surgical chapter template has been proposed. Conclusion: There is a need to consistently define and report surgical parameters from protocol development to publication as a first step to QA. A standard surgical chapter in the EORTC protocol template can help address this need. A framework to consistently implement QA for future surgical trials is needed and the rationale for this is described in this review.